2016
DOI: 10.1001/jamapediatrics.2015.4944
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Laboratory Calibration of a Serum Bilirubin Assay, Neonatal Bilirubin Levels, and Phototherapy Use

Abstract: treatment recommendations for neonatal jaundice are based on age-specific total serum bilirubin (TSB) levels. In May 2012, Ortho Clinical Diagnostics adjusted the calibrator values for Vitros Chemistry Products BuBc Slides (Ortho Clinical Diagnostics), a widely used method to quantify TSB, after concerns of positively biased results. OBJECTIVE To investigate the association between recalibration of a reflectance spectrophotometry serum bilirubin assay and TSB levels and phototherapy use among newborns. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…TSB levels were measured via the Vitros BuBc Neonatal Bilirubin method (Ortho Clinical Diagnostics, Raritan, NJ); 75.0% of study infants were born after a significant recalibration of these instruments. 11 To estimate the coefficient of variation of TSB measurements across hospitals, we used a linear mixed effects regression with facility as a random effect to model the first TSB level as a function of facility of birth, age, and other covariates (adjusted R 2 = 0.69). At a mean first TSB of 8.9 mg/dL, the SD of the first TSB level across the 16 facilities was 0.327 mg/dL (coefficient of variation = 3.7%).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…TSB levels were measured via the Vitros BuBc Neonatal Bilirubin method (Ortho Clinical Diagnostics, Raritan, NJ); 75.0% of study infants were born after a significant recalibration of these instruments. 11 To estimate the coefficient of variation of TSB measurements across hospitals, we used a linear mixed effects regression with facility as a random effect to model the first TSB level as a function of facility of birth, age, and other covariates (adjusted R 2 = 0.69). At a mean first TSB of 8.9 mg/dL, the SD of the first TSB level across the 16 facilities was 0.327 mg/dL (coefficient of variation = 3.7%).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Commercial calibrators used by field methods are known to affect the accuracy of bilirubin measurements on chemistry analyzers [13] and the clinical impact by different calibrators has been published recently. Kuzniewicz et al [14] reported that the recalibration of the BuBc method by the manufacturer in 2012 led to a 39% relative reduction in infants with a TSB level of 257 umol/L and more than 50% reduction in both birth hospital phototherapy and readmissions for phototherapy. Similarly, the implementation of a new formulation of total bilirubin by another manufacturer (Roche diagnostics) also affected neonatal phototherapy rates even compared to its previous formulation [15].…”
Section: Discussionmentioning
confidence: 99%
“…A bilirubin measurement was performed by using the Vitros BuBc Neonatal Bilirubin assay (Ortho Clinical Diagnostics, Raritan, NJ). 23,24 In May 2012, Ortho Clinical Diagnostics adjusted the calibrator values for Vitros BuBc Slides, 25 so we included an indicator variable for whether the TSB level was obtained before or after recalibration in analyses.…”
Section: Bilirubin Measurementmentioning
confidence: 99%